Assessing the potential of improving livelihoods and creating sustainable socio-economic circumstances for rural communities in Upper Egypt - Osama Ahmed; Walid Sallam (Sustainability, 2020)
Agriculture in Upper Egypt is characterized by unsustainable farming practices and a lack of the use of market intelligence. Improving agriculture in Upper Egypt is necessary, as farmers in this region need to meet the quality standards required by international markets if they are to increase export volumes. For this reason, agricultural interventions are required to transition from the current traditional farming systems and marketing practices to sustainable conservation farming practices and the use of market intelligence and logistics. The main aim of this research study is to assess the potential for improving the livelihoods of rural communities by conducting a cost–benefit analysis (CBA) and conducting a risk analysis using the Monte Carlo simulation method for the proposed agricultural interventions. Our results imply that the analyzed interventions are viable from both a financial and socio-economic point of view. The impacts of the interventions reveal real incremental employment opportunities at the farming level. In addition, the interventions have a very low probability of negative returns and become almost zero when we add the economic benefit to society.
Keywords: 330; sustainable livelihoods; socio-economic; job opportunities; cost-benefit analysis (CBA); Monte Carlo simulation; risk analysis